2002
DOI: 10.2514/2.2910
|View full text |Cite
|
Sign up to set email alerts
|

Structural Optimization of a Hat-Stiffened Panel Using Response Surfaces

Abstract: This paper describes a design study for structural optimization of an upper cover panel of a typical passenger bay of a blended wing body transport airplane. For these type of airplane the structure that obtained a common consent among designers is a sandwich structure. However unresolved issues of sandwich structures, like core crushing, might prevent their employment and suggest the study of an alternative all composite structure. A hat-stiffened laminated composite panel concept is considered as an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Only the interaction of the two kinds of stacking sequences of the laminates is dealt with here. Vitali et al have optimized these dimensions of the hat-stiffened panel [15]. The present study adopts the same dimensions of the hat-stiffened panel as shown in the research of Vitali et al As the loading condition of the present study is different from the research of Vitali et al, these dimensions are not the exact optimum but are used as reference data for the maximization of the buckling load.…”
Section: Optimization Problemmentioning
confidence: 92%
“…Only the interaction of the two kinds of stacking sequences of the laminates is dealt with here. Vitali et al have optimized these dimensions of the hat-stiffened panel [15]. The present study adopts the same dimensions of the hat-stiffened panel as shown in the research of Vitali et al As the loading condition of the present study is different from the research of Vitali et al, these dimensions are not the exact optimum but are used as reference data for the maximization of the buckling load.…”
Section: Optimization Problemmentioning
confidence: 92%
“…To release the computational burden caused by the large number of iterations, surrogate models have been successfully utilized in the optimization of stiffened panels [26][27][28].…”
Section: Surrogate-based Optimization Technologymentioning
confidence: 99%
“…While later studies have continued to address HWB flying characteristics, including noise and propulsion issues, recent years have seen an increased focus on the structural performance of the HWB. [3][4][5][6][7][8] This increased focus is due to the fact that structures technology still does not yet satisfy the expected structural capabilities required to facilitate HWB aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Several sizing and optimization studies have been conducted on HWB-like structures. 3,4,6,7 Of particular importance is the response of the non-circular HWB structure subjected to internal pressure, where double bending curvature (center and edges of the panel bending in opposite directions) is experienced by the pressurized panel that results in large local stresses that drive the panel design. This phenomenon is discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%